Letter from Kathleen Raine to Herbert Read, [1949?-1965?], [04] - http://id.worldcat.org/fast/52672 (1949)
Part of a collection of correspondence from Kathleen Raine to Herbert Read. Raine was a British scholar and poet who was awarded the Queen’s Gold Medal for Poetry in 1992. The correspondence here follows Raine’s work on a book about William Blake’s mythology. Other topics include discussion of philosophical and metaphysical subjects, and references to acquaintances in literary and arts circles.